Adjuvants Based on Hybrid Antibiotics Overcome Resistance in Pseudomonas aeruginosa and Enhance Fluoroquinolone Efficacy. (26th November 2015) - Gorityala, Bala Kishan; Guchhait, Goutam; Fernando, Dinesh M.; Deo, Soumya; McKenna, Sean A.; Zhanel, George G.; Kumar, Ayush; Schweizer, Frank
Abstract: The use of adjuvants that rescue antibiotics against multidrug‐resistant (MDR) pathogens is a promising combination strategy for overcoming bacterial resistance. While the combination of β‐lactam antibiotics and β‐lactamase inhibitors has been successful in restoring antibacterial efficacy in MDR bacteria, the use of adjuvants to restore fluoroquinolone efficacy in MDR Gram‐negative pathogens has been challenging. We describe tobramycin–ciprofloxacin hybrid adjuvants that rescue the activity of fluoroquinolone antibiotics against MDR and extremely drug‐resistant Pseudomonas aeruginosa isolates in vitro and enhance fluoroquinolone efficacy in vivo. Structure–activity studies reveal that the presence of both tobramycin and ciprofloxacin, which are separated by a C12 tether, is critical for the function of the adjuvant. Mechanistic studies indicate that the antibacterial modes of ciprofloxacin are retained while the role of tobramycin is limited to destabilization of the outer membrane in the hybrid.